2006
DOI: 10.2214/ajr.04.1915
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Dose to the Fetus from Body MDCT During Early Gestation

Abstract: Radiation doses to the fetus from institutional MDCT protocols that may be used during pregnancy (for pulmonary embolus, appendicitis, and renal colic) are below the level thought to induce neurologic detriment to the fetus. Imaging the mother for appendicitis theoretically may double the fetal risk for developing a childhood cancer. Radiation doses to the fetus from pulmonary embolus chest CT angiography are of the same magnitude as ventilation-perfusion (V/Q) scanning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
136
3
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(148 citation statements)
references
References 23 publications
5
136
3
3
Order By: Relevance
“…Besides, the embryo/fetal dose from CTPA studies has been reported to be 0.06-0.23 mGy during the third trimester of pregnancy (26), which agrees with our findings of 0.05-0.28 mGy. Discordantly, Hurwittz et al (27) reported an embryo/fetal dose of 0.24-0.66 mGy from CTPA studies performed on pregnant patients with suspected PE during the first trimester. The considerable difference between these results and our data for the first trimester, that is, 0.05-0.16 mGy, may be attributed to the considerably higher exposure settings used in the study by Hurwitz et al, that is, 140 kV-300 mAs.…”
Section: Discussionmentioning
confidence: 87%
“…Besides, the embryo/fetal dose from CTPA studies has been reported to be 0.06-0.23 mGy during the third trimester of pregnancy (26), which agrees with our findings of 0.05-0.28 mGy. Discordantly, Hurwittz et al (27) reported an embryo/fetal dose of 0.24-0.66 mGy from CTPA studies performed on pregnant patients with suspected PE during the first trimester. The considerable difference between these results and our data for the first trimester, that is, 0.05-0.16 mGy, may be attributed to the considerably higher exposure settings used in the study by Hurwitz et al, that is, 140 kV-300 mAs.…”
Section: Discussionmentioning
confidence: 87%
“…More recently, Hurwitz et al (3) estimated fetal dose by using physical measurements from internal dosimeters in an anthropomorphic phantom that was modified to represent a newly pregnant patient and a patient who was 3 months pregnant.…”
Section: Iagnostic Computed Tomographicmentioning
confidence: 99%
“…Hurwitz et al 9 estimated radiation dose to the female breast from 16-slice MDCT helical examinations using metal-oxidesemiconductor field-effect transistors ͑MOSFETs͒ in an anthropomorphic phantom. In separate efforts, Hurwitz et al 10 and Jaffe et al 11 developed methods to determine fetal radiation doses resulting from 16-slice MDCT using direct measurements of radiation-absorbed dose in an anthropomorphic phantom designed to simulate a gravid woman. More recently, Deak et al 12 estimated typical doses by calculating the energy deposition in a CTDI and anthropomorphic phantom using a collection of TLDs.…”
Section: Introductionmentioning
confidence: 99%